Trioza erytreae (Del Guercio, 1918) and the Interaction with Its Hosts: A Review - Tomás Magalhães; Amílcar Duarte; José Alberto Pereira; Natália T. Marques (Agriculture)
The cultivation of citrus in the Mediterranean region is of considerable economic importance. The viability of this industry is contingent upon a number of factors, with adequate phytosanitary management being of particular significance. During the last decade, the geographical range of the invasive psyllid, Trioza erytreae (Del Guercio, 1918), has expanded to the mainland territories of Portugal and Spain. Trioza erytreae acts as a vector for the Huanglongbing disease (HLB). This review presents the current knowledge about the hosts of the psyllid and their attractiveness and suitability. A classification of the hosts according to their suitability, as assessed in the literature, is provided. The attributes of the hosts and the methods used to assess their suitability are described, as well as the climatic factors that affect the psyllid–host interaction. The review emphasises the importance of a comprehensive evaluation of the interactions between the psyllids and their hosts to develop and implement more effective strategies for controlling T. erytreae.